Methods of Physical Evidence Verification in the Criminal Proceedings of Ukraine - B. V. Shabarovskyi (Bulletin of Kharkiv National University of Internal Affairs)
Taking into account the fact that evidence verification remains a poorly researched criminal and procedural phenomenon, and physical evidence is an important mean of establishing the circumstances of criminal proceedings, the purpose of the study was to determine and characterize the methods of verifying physical evidence in the criminal proceedings of Ukraine. To achieve this purpose, the author has set the following tasks: to analyze the provisions of the Criminal Procedural Code of Ukraine in order to identify the methods of verifying physical evidence; to determine the peculiarities of physical evidence verification. As a result of the study, the author, for the first time, has provided all the means of verifying physical evidence available to the subjects of evidence in Ukraine. The Criminal Procedural Code of Ukraine adopted on April 13, 2012, as well as the court practice have been analyzed. The author has determined the following methods of physical evidence verification in the criminal proceedings of Ukraine: comparison of physical evidence with the minutes of examination of physical evidence and its annexes (photo, video materials); verification of compliance with the provisions of the Criminal Procedural Code of Ukraine and the Resolution of the Cabinet of Ministers of Ukraine “On the Implementation of Certain Provisions of the Criminal Procedural Code of Ukraine” dated from November 19, 2012 No. 1104, which approved the Procedure for the storage of physical evidence by the prosecution, their implementation, technological processing, destruction, implementation of costs related to their storage and transfer, the safekeeping of temporarily confiscated property during criminal proceedings concerning its storage, with regard to the storage of physical evidence; examination of physical evidence by the court, familiarization with the physical evidence of the participants in the court proceedings and, if necessary, other participants in the criminal proceedings, focusing the attention of the court on those or other circumstances related to the item and its examination, which is carried out by the persons, who are subjects for the examination of physical evidence; putting questions about physical evidence to witnesses, experts, specialists who inspected the item and responding these questions; comparison of physical evidence with other evidence in order to ascertain their admissibility and credibility.